Efektivitas Pemakaian Zeolit Sebagai Media Biofilter Dalam Menurunkan Polutan Organik Limbah Cair Tahu - Budijono '; M. Hasbi; Ahmali ' (Ilmu Perairan (Aquatic Science), 2010)
The objective of this study is to assess the influence of zeolit biofilteraplication in degrading organic pollutant in waste of tofu industry at combinationanaerobic-aerobic system. This study was carried out in tofu industry at Tampanregion, Pekanbaru. The total amount of wastewater that produced from one smalltofu industry is around 15-20 m3/day, and now is collected in wastewater drainage.Basically this wastewater treatment relies on bacteria in degrading pollutants. Theuse of zeolit is to increase specific surface of media for attaching bacteria. Thesystem consist of one reactor that is made of 5 mm glass, and the volume reactor 140liters. The reactor was equipped with one circulating pump and blower in the aerobiczone. It took 3 weeks for seeding micoorganism.The raw water used in this experiment is waste water from tofu industriesthat have organic compound around 1554 - 2539 mg/l. The water for physical andchemical analysis is sampled daily. It took from raw water and anaerobic-aerobiccolum of reactor. The results showed that the zeolit biofilter gives a big influence todegrade organic pollutant. The efectivity process in decreasing organic compundvalue ± 90% better than non zeolit biofilter.